Low humidity air drying of apple slices: Effect of EMR pretreatment on mass transfer parameters, energy efficiency and quality. (July 2019) - Shewale, Sandhya R.; Rajoriya, Deependra; Hebbar, H. Umesh
Abstract: The apple slices were treated with electromagnetic radiations (EMR) namely, infrared (IR) and microwave (MW) and dried using low humidity air (LHA) and normal hot air (HA) at 40 °C. The effect of EMR pretreatment on drying kinetics, mass transfer, shrinkage, porosity, energy efficiency and product quality was evaluated. The combination of EMR pretreatment with LHA drying reduced the drying time by 23.4 to 27.3%, and the dried product had lower shrinkage (60 to 65%) as well as higher porosity (0.38 to 0.45) compared to control. Among the EMR pretreatments, IR treated slices retained a higher amount of ascorbic acid (78.68%), phenolic content (74.42%), antioxidant activity (79.54%) and better color compared to MW treated. EMR pretreatment reduced the energy requirement for drying by 26.5 to 37.1%. The mass transfer parameters (moisture diffusivity and mass transfer coefficient) estimated using the analytical model proposed by Dincer and Dost showed higher values for EMR treated samples. Moisture content predicted for both the drying methods showed good agreement with experimental values. The present study demonstrated that for heat sensitive products like apple, a combination of IR pretreatment and LHA drying could be effective for reducing drying time as well as energy requirements and also to obtain better quality products. Highlights: Combining EMR pretreatment with LHA reduced drying time by 27.3%. EMR pretreatment intensified mass transfer during drying. IR pretreatment and LHA drying increased porosity and reduced shrinkage. LHA drying resulted in better retention of ascorbic acid and polyphenols. Energy consumption reduced by ~37% as compared to HA drying.